A Synthetic Nanoparticle Based Vaccine Approach Targeting MSP4/5 Is Immunogenic and Induces Moderate Protection Against Murine Blood-Stage Malaria - Wilson, Kirsty L.; Pouniotis, Dodie; Hanley, Jennifer; Xiang, Sue D.; Ma, Charles; Coppel, Ross L.; Plebanski, Magdalena (Frontiers in Immunology, 2019)
Malaria remains a significant health problem in many tropical and sub-tropical regions. The development of vaccines against the clinically active blood-stage of infection needs to consider variability and polymorphism in target antigens, and an adjuvant system able to induce broad spectrum immunity comprising both antibodies and helper T cells. Moreover, recent studies have shown some conventional pro-inflammatory adjuvants can also promote expansion of immunosuppressive regulatory T cells (Treg) and myeloid derived suppressor cells (MDSC), both of which could negatively impact malaria disease progression. Herein, we explore the ability of a model nanoparticle delivery system (polysterene nanoparticles; PSNPs), previously proven to not induce conventional inflammation, Treg or MDSC, to induce immunity to MSP4/5 from Plasmodium yoelii, a member of the MSP4 and MSP5 family of proteins, highly conserved across diverse malaria species including P. falciparum. The results show PSNPs-MSP4/5 conjugates are highly immunogenic, inducing immune responses comprising both T helper 1 (Th1) and Th2 cellular immunity, and a spectrum of antibody subclasses including IgG1, IgG2a and IgG2b. Benchmarked against Alum and Complete Freund’s Adjuvant (CFA), the immune responses that were induced were of comparable or higher magnitude, for both T cell frequencies by ELISpot and antibody responses in terms of end titer. Importantly, immunization with PSNPs-MSP4/5 induced partial protection against malaria blood-stage infection which was shown to be mechanistically dependent on interferon gamma (IFN-γ) production. These results expand the scope of adjuvants considered for malaria blood-stage vaccine development to those that do not use conventional adjuvant pathways and emphasizes the critical role of cellular immunity and specifically IFN-γ producing cells in providing modest protection against blood-stage malaria.